Clinical application of interventional techniques in the treatment of Budd-Chiari syndrome - 徐克 冯博 钟红珊 张曦彤 苏洪英 李红 赵钟春 张汉国 (Chinese medical journal, 2003)
Objective To evaluate the clinical value of various kinds of interventional techniques in the treatment of Budd-Chiari syndrome (BCS).Methods Multiple techniques such as recanalization of the inferior vena cava (IVC) under the guidance of marker and multi-angled fluoroscopy, recanalization of the hepatic vein with a transjugular approach, PTA, Z-expandable metallic stent (Z-EMS) implantation and modified TIPSS were used to treat 103 patients with BCS.Hesults Of 103 patients with BCS, 59 patients with obstruction of IVC were treated using recanalization of IVC. Seventeen patients with hepatic vein obstruction had their hepatic veins recanalized. The rest of the patients were given other methods of interventional treatment. Of all the subjects, 101 successfully underwent their procedures, with a success rate of 98.06% ; and only 2 failed to recanalization of the IVC. Fifty-three patients were treated using PTA for the first time, with a success rate of 100%. In the 48 patients undergoing Z-EMS implantation for the first time, the success rate was 95.8%. Five patients were treated with modified TIPSS. After these interventional treatments, the success rate was 100%. Two patients died 16 h and 72 h respectively after operation because of DIC and severe hemoptysis. SevenS-two patients were followed up for 1 -94 months (with a mean of 42. 3 months). The mean follow-up of a BCS patient treated with PTA was 52. 1 months, resulting in a primary patent rate of 59.4% and a restenosis rate of 40. 6%. The mean follow-up of BCS treated with stenting was 33.5 months, with a primary patent rate of 87.5% and a restenosis rate of 12. 5%. Eight patients died 7 -64 months after the interventional procedure.Conclusion Flecanalization of IVC or the hepatic vein transjugularly, PTA, Z-EMS implantation and modified TIPSS can be regarded as safe and effective micro-invasive methods in the treatment of BCS.